2021
DOI: 10.1111/cdev.13570
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Neighborhood Ethnocultural Context and the Mental Health of Mothers and Children in Low‐Income Mexican American Families

Abstract: Socioeconomically disadvantaged neighborhoods increase the risk for poor mental health among residents, yet protective factors may operate alongside risk. This study evaluated the influence of the prenatal neighborhood ethnocultural context on child behavior problems and maternal depressive symptoms. Prenatal maternal role expectations, prenatal culture-specific stress, and postpartum depression (PPD) symptoms were evaluated as mediators. Participants included 322 low-income, Mexican American mother-child dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Alternatively, an association between discrimination and depressive symptoms may emerge when evaluating individuals living in more diverse neighborhoods. Although our neighborhood cultural cohesion measure was normally distributed, the majority of the current sample of women lived in neighborhoods with high percentages of Hispanic/Latinx residents (Curci et al, 2021). Further, less economic hardship was correlated with more neighborhood cultural cohesion, suggesting that neighborhood support may target women’s material burdens rather than mental health among the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, an association between discrimination and depressive symptoms may emerge when evaluating individuals living in more diverse neighborhoods. Although our neighborhood cultural cohesion measure was normally distributed, the majority of the current sample of women lived in neighborhoods with high percentages of Hispanic/Latinx residents (Curci et al, 2021). Further, less economic hardship was correlated with more neighborhood cultural cohesion, suggesting that neighborhood support may target women’s material burdens rather than mental health among the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, cultural‐developmental neighborhood effects research documents that Latinx neighborhood concentration confers benefits to cultural and linguistic development (Lutz, 2006; Safa et al, 2019; White et al, 2017), social development (Molnar et al, 2003); socio‐emotional development (Curci et al, 2021; Lee & Liechty, 2015), and social‐cognitive development (Safa et al, 2019; White, Knight, et al, 2018) among Latinx (predominantly Mexican‐origin) youths. Black neighborhood concentration has demonstrated benefits for social development (Hurd et al, 2013; Stevenson et al, 2005), socio‐emotional development (Hurd et al, 2013), socio‐cognitive development (Ochieng, 2011; Stevenson et al, 2005), and birth outcomes (Madkour et al, 2014) among Black youth.…”
Section: Instantiating Culturally and Contextually Informed Investiga...mentioning
confidence: 99%
“…The literature ties structural contexts to both costs and benefits for youth. For example, whereas much of this research links concentrated poverty to negative outcomes, research has also documented some positive outcomes of majority‐Black or majority‐Latinx spaces (Byrd & Chavous, 2009; Curci et al, 2021; Seaton & Yip, 2009). This is emphatically not to argue that structural segregation is positive, but rather, to highlight aspects of pervasive structural racism in which some activity spaces that act as “racial safe spaces” can be beneficial for young people of color.…”
Section: Structures and Processes In Neighborhood Research On Youth D...mentioning
confidence: 99%
“…Subjective measures are critical here as there is growing evidence to suggest that perceptions over actual neighborhood characteristics may impose greater influence on mental health, particularly in minoritized families [ 22 , 26 – 30 ]. In other work characterizing Latino mental health, scholars have shown that within Mexican American mother–offspring dyads, the subjective neighborhood, or how mothers perceive their neighborhoods and neighbors’ attitudes to them, relayed valuable information regarding their acceptance of them and their culture [ 29 , 31 ]. Other aspects of neighborhoods, including cohesion and sociality, have also been shown to positively impact residents’ mental health [ 29 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic homogeneity lends itself to enabling trust among neighbors and increased social capital, thereby benefiting residents [ 50 ]. Consistent with the social disorganization theory, Latinos living in homogenous neighborhoods tend to have more social cohesion [ 32 ], better adolescent mental health [ 49 , 51 ], and prenatal mental health [ 31 ] compared to ethnically heterogeneous neighborhoods. Notably, Curci and colleagues [ 31 ] found that a higher Latino neighborhood concentration promotes positive maternal mental health outcomes and child health outcomes among 322 Mexican American mother–offspring dyads from low-income neighborhoods in Phoenix, Arizona.…”
Section: Introductionmentioning
confidence: 99%